Emergence of an oceanic CO2 uptake hole under global warming. - Lee, Huiji; Noh, Kyung-Min; Oh, Ji-Hoon; Park, So-Won; Shin, Yechul; Kug, Jong-Seong (Nature Communications, 2025)
The ocean is a crucial sink for anthropogenic CO2 emissions, yet its future response remains uncertain. Here, using the Community Earth System Model (CESM2) under different CO2 emission rates, we find a pronounced weakening of ocean CO2 uptake in the Subpolar North Atlantic (SPNA), distinct from the global response. Initially, the SPNA is an effective CO2 sink, but due to the contraction ofdeep convection, the uptake decreases and the oceanic pCO2 exceeds the global average. Recognizing the importance of regional ocean circulation in CO2 uptake, we identify a nonlinear relationship between environmental conditions and uptake response, revealing consistent thresholds for the emergence of uptake weakening. These findings are also reproduced in the Coupled Model Intercomparison Project Phase 6, confirming their robustness. Overall, the distinct uptake response reflects the key role of regional dynamics in regulating the CO2 budget and geochemical environment,which is important for regional CO2 mitigation strategies.